Legal Due Diligence of Fintech Agreement Law Transformation of Economic Recovery in the New Normal Era - Yapiter Marpi (HUMAYA Jurnal Hukum Humaniora Masyarakat dan Budaya, 2021)
Today, business transactions no longer have to be carried out face to face, instead through virtual or in a virtual world that is connected globally. One of the economic activities that affect the public interest is the activity of channeling funds which must be carried out fairly and in accordance with Article 33 paragraph (4) of the 1945 Constitution, namely the economy. Financing Institutions have undergone a process of digitization, plus during the Covid-19 pandemic experienced a high surge in business capital needs so that financing transactions can be easily accessed online, financial technology (fintech) services are regulated in OJK Regulation No.77 / POJK.01 / 2016 concerning Borrowing Services Information Technology-Based Borrowing If the provider of Information Technology-Based Borrowing and Lending Services has been proven to have committed a violation, it may result in imposing sanctions on the agreement. The purpose of this research is to contribute from a conceptual perspective of business law in fulfilling economic recovery and to find out about sanctions arrangements for Fintech service providers in order to achieve legal certainty. The research method used is through normative law and conceptually socio legal. The results of this research analysis are expected that business people want to invest in a company with a fast process, so the need for Fintech services is to be able to transform in a Legal Due Diligence so that the economic recovery of a new national era is held based on economic democracy using the principles of togetherness, justice, sustainability, environmental awareness, independence. Legal Due Deligence is able to be a solution to minimize potential risks in the future. So that it will get benefits for finctech organizers and the public who use services as a result of the positive influence due to the Legal Due Deligence business concept.